Antagonistic indirect interactions between large and small conspecific prey via a heterospecific predator. Issue 2 (15th June 2015) - Yamaguchi, Aya; Kishida, Osamu
Abstract : Intrapopulation size variation strongly influences ecological interactions because individuals belonging to different size groups have distinct functions. Most demonstrations of the impacts of size variation in trophic systems have focused on size variation in predator species, and the consequences of size variation in prey species are less well understood. We investigated how prey size structure shapes intra‐ and interspecific interactions in experiments with a gape‐limited predator (larvae of the salamander Hynobius retardatus ) and its heterospecific prey (frog tadpoles, Rana pirica ). We found that large and small tadpole size groups each increased mortality in the other group by intensifying salamander predation; this type of indirect interactions is called apparent competition. The antagonistic impacts on the prey size groups were caused by different size‐specific mechanisms. By consuming small tadpoles, the salamanders grew large enough to consume large tadpoles. The activity of large tadpoles, by increasing the activity of the small tadpoles, may increase the number of encounters with the predator and thus small tadpole mortality. These results suggest that the magnitude of a predator's ecological role, such as whether a top–down trophic cascade is initiated, depends on size variation in its heterospecific prey.